(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the productivity and architecture of Ilex paraguaiensis under different soil cover and fertilization dosages. The treatments were: Crotalaria juncea L., hog bean (Canavalia ensiformis L.), dwarf pigeon pea (Cajanus cajan L) and Urochloa ruziziensis. Five different doses of NPK mineral fertilizer were used, equivalent to 0 kg, 100 kg, 200 kg, 400 kg and 800 kg ha-1. The design was in randomized blocks with subdivided plots. The evaluations were submitted to analysis of variance and the means to the Tukey test (p <0.05). Fertilization levels were assessed by regression analysis. The results show that the use of green manure allows a significant increase in the development of Ilex paraguaiensis plants, indicating that their use by small producers can potentially increase the profitability of this crop.